1969
DOI: 10.1042/bj1130501
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of bacterial flagellin with cyanogen bromide. Antigenic properties of the protein fragments

Abstract: 1. Four polypeptide fragments, obtained by cyanogen bromide treatment of the protein flagellin from Salmonella adelaide, were tested for their antigenic activity by using them as inhibitors in three different assays: bacterial immobilization, haemagglutination of sensitized erythrocytes and quantitative micro precipitation. Immunodiffusion studies were also performed on the protein fragments. 2. Cleavage of the flagellin molecule in this way gave no detectable loss of antigenic determinants. Fragment A (mol.wt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

1971
1971
2010
2010

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…3, there emerges a strong correlation between the ability of a mAb to bind to a peptide derived from the globular protein antigen, rat cyt c, and the specificity of that mAb for a denatured form of the protein. Antibodies (26,27). In fact, this distinction was the basis for the early classification of epitopes as either sequential or conformational (28).…”
Section: Discussionmentioning
confidence: 99%
“…3, there emerges a strong correlation between the ability of a mAb to bind to a peptide derived from the globular protein antigen, rat cyt c, and the specificity of that mAb for a denatured form of the protein. Antibodies (26,27). In fact, this distinction was the basis for the early classification of epitopes as either sequential or conformational (28).…”
Section: Discussionmentioning
confidence: 99%
“…18,000) (6). Precise antigenic studies in the preceding paper (1) have demonstrated that CNBr-digested flagellin has a slightly reduced affinity for anti-flagellin antibodies (Krel = 5.7 X 10-1).…”
Section: Cyanogen Bromide Digest Of Flagellin: Earlier Work In This Lmentioning
confidence: 99%
“…The flagellar filament is composed of a single protein, flagellin. The flagellin proteins of E. coli and several other species are conserved in their terminal regions, while the central region is variable and carries H-serotype-specific epitopes (9,17,22,39,40). The structure of the Salmonella enterica LT2 flagellum is known from electron microscopy, X-ray fiber diffraction, and X-ray crystallography.…”
mentioning
confidence: 99%